PERANCANGAN PEMBANGKIT LISTRIK TENAGA GELOMBANG LAUT DAN SURYA SEBAGAI SOLUSI MENGATASI KELANGKAAN ENERGI LISTRIK DI DAERAH PESISIR - Utsman, Faqih; Catur Wibowo, Bagus; Meka Mutya Fhadilla, Putri; Ishac Einstein Simanjuntak, Albert (Universitas PGRI Semarang, 2022)
Hybrid Power Plants are prototypes of ocean wave and solar power plants based on vertical rotors and solar panels. Hybrid Power Plants are motivated by petroleum production, the lack of equitable distribution of electrical energy on the most underdeveloped area in Indonesia, and the government's latest energy mix targets regarding solar and ocean wave energy. Based on the geographical location, Indonesia has the potential for ocean waves and solar energy. Hybrid Power Plants based on vertical rotors and solar panels aim to overcome the scarcity of electrical energy in coastal areas. The vertical rotors and solar panels in this prototype are influenced by the characteristics of the ocean wave height and the intensity of sunlight. In this program using the methods of literature study, design, manufacture of prototypes, and testing. The prototype has a working principle of converting solar energy into DC voltage, the DC voltage flows into Solar Charge Controller to be maximize battery charging. In addition, the vertical rotor converts the motion of ocean wave into AC voltage, the AC voltage flows into rectifier and filter to be a DC voltage that can be charged into battery. Both of which can then be used by fishermen for their daily electricity needs. The results of the solar panel test at 1 PM get the output with a voltage of 14.21V and a current of 2.46A. Meanwhile, from the vertical rotor simulation results, the output voltage data is 17.19V with a period of 0.03s. With the results of these tests, it is hoped that this prototype can be a solution to overcome the scarcity of electrical energy in the coastal area and in the future it can be done to increase the prototype so that the output can be increased and can be used for many fishermen needs.Keywords : Hybrid Power Plants, solar panels, vertical rotors, testing, rarity.